2020
DOI: 10.1039/d0ra01319f
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for enhanced activity of doxorubicin on co-delivery with octa(3-aminopropyl)silsesquioxane

Abstract: The interaction between polyhedral oligomeric silsesquioxane (POSS) and doxorubicin, leading to formation of active complexes involving POSS functional aminopropyl groups and anthracycline functional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The novel complexes are inexpensive to prepare, more effective than free drugs at low systemic toxicity. We found POSS(OH) 32 to be another useful silsesquioxane [16] that increased the efficacy of anthracyclines. These findings leads to the hypothesis that such cage-type silsesquioxanes with various functional groups can serve as effective nanocarriers in drug delivery.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The novel complexes are inexpensive to prepare, more effective than free drugs at low systemic toxicity. We found POSS(OH) 32 to be another useful silsesquioxane [16] that increased the efficacy of anthracyclines. These findings leads to the hypothesis that such cage-type silsesquioxanes with various functional groups can serve as effective nanocarriers in drug delivery.…”
Section: Discussionmentioning
confidence: 89%
“…In both these reports, the authors proposed NH• • • N hydrogen bonding as a driving force for complex (aggregate) formation; however, at that time, it was only an experimentally unsupported suggestion. Our recent study revealed that not only hydrogen bonding but also electrostatic interactions and π-π stacking between DOX moieties play important roles in the formation of weak complexes [16]. Thus, studies on potential formation of active complexes involving POSS with various functional groups and the anthracycline functional groups also appear generally important for other anti-cancer drug complexing systems, once the presence of required functional groups for such interactions with POSS are identified.…”
Section: Introductionmentioning
confidence: 95%
“…FTIR spectroscopy was additionally used for structural characterization of the conjugates formed via ester bond between drugs and the POSS carrier. FTIR spectra of conjugates differed from that of SAMDOX/SAMDAU [ 11 ]. The spectra of conjugates 4 – 9 ( Figure 9 ) show a new absorption frequency at ~1734 cm −1 (ν C=O , ester bond) indicating formation of an ester bond between SAMDOX/SAMDAU and the POSS hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they show longer release time, which makes them potential candidates for biomedical applications in anticancer therapy. POSS type nanocarriers were proven again [ 10 , 11 ] to be useful systems in formation of nanoconjugates and nanocomplexes with anthracycline drugs. The present work shall be expanded by in vitro studies as soon as the test laboratory reopens after COVID-19 closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation